From end-of-life tires to storable energy carriers. (15th December 2020) - Niezgoda, A.; Deng, Y.; Sabatier, F.; Ansart, R.
Abstract: End-of-life tires are an increasingly important environmental burden. Since retreading is only partly possible, safe and economic methods of disposal need to be developed. Pyrolysis of ELTs, and subsequent upgrading/application of the produced energy carriers, is considered a valuable treatment method. In order to design the process, numerous operation units have to be taken into account. Char, vapour and gas are formed in the reactor. The char is purified from ZnO with a leaching process. The pyrolysis vapour is separated into a condensable fraction (oil) and a non-condensable fraction (gas) thanks to a cross-flow condenser with air as indirect cooling medium. The remaining gas is compressed to 6 bar: a part of it is continuously converted in electricity for process use, while another part is stored for power generation at peak demand time. A flowsheet of the process is established and environmental and assessment of investments and production are discussed. For the pyrolytic treatment of 3 ton/hr of ELTs, the required heat for the reactor is 271 kW at 380 °C, provided by electrical heating elements. A reactor volume is determined for a residence time of about 6 h. For the cross-flow condenser, indirectly air-cooled, a heat-transfer area of about 13.2 m 2 is required. The compression of the gas the pressurized pyrolytic gas storage tank depends upon the excess pyrolytic gas produced during operation. The char cooler requires a heat-transfer area of 10.2 m 2, when indirectly cooled by water. Operating parameters of the leaching and subsequent recovery of Zn 2+ complete the design. The product added-value and the large-scale capacity make the process economically viable, although the ROI is between 2 and 3 years. Graphical abstract: Image 1 Highlights: Once a tire has been used and cannot be retreaded, it becomes an end-of-life tire (ELT). Because of the many components present in tires, their recycling is difficult. Pyrolysis can produce energy carriers and allows to recover 71% of the energetic capacity of the tires. The pyrolysis plant for 3 ton/hr of ELT is studied and designed in detail. Novel techniques for product upgrading are discussed.